New Directions in Gaucher Disease. Issue 11 (21st August 2016) - Horowitz, Mia; Elstein, Deborah; Zimran, Ari; Goker‐Alpan, Ozlem
Abstract : In the present review we focus on four areas of interest: Cellular disfunction in Gaucher disease; The association of Gaucher disease with Parkinson disease; Treatment modalities in Gaucher disease and the use of induced pleuripotent stem cells to study Gaucher disease. ABSTRACT: In Gaucher disease (GD), mutant lysosomal acid β‐glucocerebrosidase fails to properly hydrolyze its substrate, glucosylceramide, which accumulates in the lysosomes. Due to its phenotypic heterogeneity, GD has been classified into type 1, non‐neuronopathic, and types 2 and 3, the neuronopathic forms, based on the primary involvement of the central nervous system. Neuroinflammation and necroptotic death may appear in the neuronopathic forms of GD, whereas type 1 GD patients may develop Parkinson disease (PD), a prototype of protein misfolding disorders of the nervous system. PD is significantly more prevalent among GD carriers and patients than among the non‐GD populations. It is apparent that the amount of mutant enzyme present in lysosomes depends on the amount of mutant enzyme recognized as correctly folded in the endoplasmic reticulum (ER) for physiologically correct transport through the Golgi apparatus to the lysosome. Mutant enzyme recognized as misfolded is retained in the ER, inducing the Unfolded Protein Response. In the current review, we present three discrete areas of interest: molecular and cellular mechanisms underlying the association between GD and PD; the clinical and genetic associations between GD and PD; and treatment options for GD. We also discuss the relevance of induced pleuripotent stem cells to the above associations.